Efficiency and Equity Performance of a Coordinated Ramp Metering Algorithm - Li, Duo; Ranjitkar, Prakash; Zhao, Yifei (Promet - Traffic&Transportation, 2016)
Ramp metering (RM) has been widely applied due to its effectiveness in improving motorway traffic conditions by limiting inflow from on-ramps. A great deal of experimental and simulation-based studies have proven system-wide benefits of motorways from RM. Benefits attributed to RM in the literature include reducing travel times, increasing motorway throughputs and decreasing fuel consumption and emissions. However, RM benefits might be costing more some motorway users, e.g. some on-ramp users might be experiencing longer delay than others, which leads to an unfair allocation of RM benefits. This paper presents a coordinated ramp metering strategy, which is aimed at reducing the inequity among motorway users using different on-ramps and investigates trade-offs between efficiency and equity for the proposed strategy. Total travel time is used to measure the efficiency while Gini coefficient is used to measure equity. A combined index is proposed incorporating the two measures to serve as an objective function to solve the bi-objective control design problem. The performance of the proposed strategy is verified by comparing it to a well-established coordinated ramp metering strategy HERO using micro-simulation software AIMSUN. Simulation results revealed that the equity of the motorway system can be improved significantly by using the proposed strategy without compromising much on the efficiency of the system.